Economic dimensions of responsible consumer behavior in sustainable development - Liashenko, Oksana; Demianiuk, Olga (Видавничий дім «Гельветика», 2025)
Addressing the global imperative of sustainable development requires a comprehensive, data- driven understanding of how individuals make consumption decisions when personal economic incentives conflict with broader collective ecological interests. This study investigates the behavioural mechanisms underpinning responsible consumer choices by integrating social preference theory with decision- framing effects. The research employs the Quantal Response Equilibrium (QRE) framework, accommodating bounded rationality and probabilistic strategic behaviour, to model the dynamic interaction between private utility and environmental responsibility. A behavioural experiment involving 215 participants was conducted using the oTree experimental platform. The study incorporated the Social Value Orientation (SVO) Slider Measure to elicit individual prosocial preferences and a ten- round interactive “Green Consumer Game,” in which participants chose among strategies differing in personal payoff levels and ecological consequences, under either gain (reward) or loss (penalty) framing conditions. QRE- based choice probabilities were calibrated using maximum likelihood estimation of the rationality parameter within logit models implemented in Python. The empirical findings demonstrate that individuals with stronger social preferences are significantly more likely to choose environmentally responsible strategies. Framing has a robust effect: reward- based framing was considerably more effective in promoting pro- social decision- making than penalty- based framing. The QRE model achieved superior predictive accuracy compared to the classical Nash Equilibrium (RMSE 0. 069 vs. 0. 079), validating its empirical utility in ethically constrained decision contexts. This study' s novelty and theoretical value lie in applying QRE to ecologically motivated dilemmas, offering a quantitative assessment of how moral preferences and framing jointly shape consumer choice under uncertainty. Its practical contribution provides policymakers and sustainability practitioners with actionable insights for designing behavioural interventions, incentive schemes, and strategic messaging to encourage sustainable consumption across diverse socioeconomic environments.
Keywords: behavioural economics; responsible consumer behaviour; sustainable development; social preferences; experimental economics